Analysis of Heavy Metals Concentration in Textile Wastewater in Batik Industry Center - Dwi Astuti; Normah Awang; Mohd Sham Bin Othman; Nurul Farahana Binti Kamaludin; Chan Kok Meng; M. Mutalazimah (Jurnal Penelitian Pendidikan IPA, 2023)
The textile industry is the main source of environmental pollution in terms of quality and quantity. It consumes large amounts of water (200 m3/ tonne of products), and around 90% of the quantity is wastewater. Improper disposal of textile wastewater will cause serious environmental problems due to the presence of heavy metals in the waste which will adversely affect aquatic organisms. To analyze, the concentration of heavy metals in textile (batik) wastewater was collected from 15 small, medium, and large-scale textile industry waste disposal centers located at the Batik Industry Center of Kampoeng Batik Laweyan Surakarta, Indonesia August 2019. Standard methods of 22nd Edition 2012 APHA -AWWA-WEF with inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to analyze the concentration of Iron (Fe), Copper (Cu), Chromium (Cr), Cadmium (Cd), Lead (Pb) and Nickel (Ni) in the sample. The results of the analysis showed that from 15 sample locations, several locations had levels of Cu, Pb, Ni, Cr, and Cd below the detection limit, i.e.  2 (<0.01 ppm), 13 (<0.02 ppm), 13 (<0.01 ppm), 15 (<0.01 ppm), and 15 (<0.02 ppm) locations for each metal respectively, while Fe levels were above the detection limit at all locations. The mean levels and number of locations for Fe, Cu, Pb, and Ni were 2.63 ± 5.01 (n = 15), 0.48 ± 0.99 (n = 13), 0.05 ± 0.03 (n = 2) and 0.02 ± 0.00 (n = 2) and the ranges of each metal level were 0.07-19.4 ppm, 0.01-3.73 ppm, 0.02-0.07 ppm, and 0.01-0.02 ppm respectively. Among these heavy metals, the highest concentration was Fe, and all samples had Cr and Pb levels below the detection limit. By comparing the results of this study with the safe limit for industrial wastewater according to Central Java Provincial Regulation No. 5 of 2012, only wastewater originating from two sampling locations can be used for irrigation and aquaculture, namely at locations B2 and B5